Vortex‐Dominated Aeolian Activity at InSight's Landing Site, Part 2: Local Meteorology, Transport Dynamics, and Model Analysis. Issue 4 (7th April 2021) - Baker, M.; Newman, C.; Charalambous, C.; Golombek, M.; Spiga, A.; Banfield, D.; Lemmon, M.; Banks, M.; Lorenz, R.; Garvin, J.; Grant, J.; Lewis, K.; et al.
Abstract: Geologic and climatic processes on modern‐day Mars are heavily influenced by aeolian surface activity, yet the relationship between atmospheric conditions and sediment mobilization is not well understood. The Interior Exploration using Seismic Investigations, Geodesy, and Heat Transport (InSight) spacecraft is uniquely able to address this issue, due to its joint imaging and continuous high‐frequency meteorological capabilities, which allow for direct comparison between surface activity and atmospheric conditions. Since landing in the volcanic plains of Elysium Planitia, InSight's camera's have recorded intermittent, small‐scale surface changes, including removal of fine material on the lander footpad, linear tracks and localized surface darkening caused by minor dust removal, and surface creep of granules, as presented in Part 1 (Charalambous et al.,  2021, this issue). Surface activity is found to correlate well with the timing of abrupt pressure drops (Δ P  ∼ 1–9 Pa) and transient wind gusts ( v  ∼ 14–31 m/s) associated with convective vortex passage. Here we identify the major erosive forces acting on surface particles during these events, including the vertical pressure gradient force at the vortex core and the drag force generated by quickly‐rotating tangential winds. Orbital and ground‐truth data suggest that aeolian activity at InSight's landing site is sporadic under modern climatic conditions. Ongoing aeolian surface modifcation is driven primarily by turbulent vortices that sporadically lift dust and redistribute coarser sediment (i.e., sand and granules) but do not aid in the development of organized aeolian bedforms. Surface erosion is localized within the path these vortices take across the surface which is controlled by seasonally‐reversing background circulation patterns. Plain Language Summary: Numerous orbiting and landed spacecraft have imaged wind‐driven ("aeolian") motion of sand and dust on Mars. However, spacecraft on the surface have generally lacked the instrumentation required to interpret the atmospheric conditions driving this motion. Here we utilize the unique opportunity provided by the NASA InSight lander's joint imaging and meteorological capabilities to closely interpret ongoing aeolian activity at the spacecraft's landing site at Elysium Planitia and similar plains regions across Mars. During the first 400 martian days (sols) of the mission, intermittent, small‐scale motion of dust and sand are observed in association with local, thermally driven vortices passing over or near the lander. In situ data are also compared to orbital images and atmospheric model predictions to obtain a more comprehensive picture of wind‐related processes across the region. Overall, aeolian surface modification at this location is found to be very limited under current climatic conditions and is likely dominated by redistribution of fine material caused by transient convective events. Key Points: NASA's InSight mission provides a chance to study aeolian transport through concurrent imaging and high‐frequency atmospheric monitoring The surface at InSight's landing site is generally stable besides intermittent surface activity caused by convective vortex passage The vertical pressure gradient within the vortex core and increased drag caused by rotational winds help facilitate surface erosion